2015
DOI: 10.1177/0956462415584489
|View full text |Cite
|
Sign up to set email alerts
|

Distance from care predicts in-hospital mortality in HIV-infected patients with severe sepsis from rural and semi-rural Virginia, USA

Abstract: There are few data regarding outcomes from severe sepsis for HIV-infected patients living in rural or semi-rural settings. We aim to describe the characteristics and predictors of mortality in HIV-infected patients admitted with severe sepsis to the University of Virginia located in semi-rural Charlottesville, Virginia, USA. We queried the University of Virginia Clinical Data Repository for cases with ICD-9 codes that included: (1) infection, (2) acute organ dysfunction, and (3) HIV infection. We reviewed each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Many studies have shown the reverse associations between the survival probability of time-sensitive cardiovascular disease and geographical distance to emergency medical centers [8-10, 12, 27]. The adverse mortality effects of a long travel distance to hospital were also observed in cases of sepsis and injuries (e.g., traumatic brain injury) [11,28,29]. In addition, our risk-adjusted analysis also suggested that distance decay affects the survival probability of these five ECSCs.…”
Section: Plos Onesupporting
confidence: 57%
“…Many studies have shown the reverse associations between the survival probability of time-sensitive cardiovascular disease and geographical distance to emergency medical centers [8-10, 12, 27]. The adverse mortality effects of a long travel distance to hospital were also observed in cases of sepsis and injuries (e.g., traumatic brain injury) [11,28,29]. In addition, our risk-adjusted analysis also suggested that distance decay affects the survival probability of these five ECSCs.…”
Section: Plos Onesupporting
confidence: 57%
“…Driving is the main source of transportation for Los Angeles County residents, yet 31% of our SES quintile-1 cohort lived in neighborhoods where an estimated quarter of residents lack access to a vehicle. 13 Previous reports similarly found higher mortality risk among patients with severe sepsis who lived far from care 30 or who resided in a medically underserved area. 31 Lack of access to ambulatory services may also lead to a high frequency of emergency department visits, especially in the homeless population.…”
Section: Discussionmentioning
confidence: 90%
“…Prior studies also had noted the importance of distance to ART facility. For instance, several prior studies found distance to health facility influenced uptake of prevention regimens [44], high mortality [45], and visiting times [46]. A study conducted in rural Malawi suggested that reduction in travel distance could achieve the ART coverage and increase access to ART [47].…”
Section: Key Explanationsmentioning
confidence: 99%